2014
DOI: 10.3390/atmos5020420
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Abundances, Trends and Emissions of CFC-216ba, CFC-216ca and HCFC-225ca

Abstract: Abstract:The first observations of the feedstocks, CFC-216ba (1,2-dichlorohexafluoropropane) and , as well as the CFC substitute HCFC-225ca (3,3-dichloro-1,1,1,2,2-pentafluoropropane), are reported in air samples collected between 1978 and 2012 at Cape Grim, Tasmania. Present day (2012) mixing ratios are 37.8 ± 0.08 ppq (parts per quadrillion; 10 15 ) and 20.2 ± 0.3 ppq for CFC-216ba and CFC-216ca, respectively. The abundance of CFC-216ba has been approximately constant for the past 20 years, whilst that of CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…However, the highest mole fractions of the flights in late 2013 slightly exceed the monthly mean values at the in situ stations (Figures and S1). This can have been partly caused by a lag of the declining trend due to the transit time of surface air massess to these altitudes (>11 km) or by input from fresh pollution, which was also found for some other compounds in some of these samples [ Kloss et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the highest mole fractions of the flights in late 2013 slightly exceed the monthly mean values at the in situ stations (Figures and S1). This can have been partly caused by a lag of the declining trend due to the transit time of surface air massess to these altitudes (>11 km) or by input from fresh pollution, which was also found for some other compounds in some of these samples [ Kloss et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…The discovery of HCFC‐31 in the global background atmosphere during this study and other examples of recently found, nonreported substances [ Kloss et al , ; Laube et al , ; Vollmer et al , ], highlights the necessity of a continuous top‐down monitoring of feedstock, intermediates, and products, even if production processes are designed not to lead to such emissions. Therefore, HCFC‐31 should be further monitored to ensure that its decline continues and additional efforts are needed to isolate the specific emission sources.…”
Section: Resultsmentioning
confidence: 99%
“…In 2012, they reached mole fractions of 219.8 ppt (parts per trillion, 10 −12 ), 22.5 ppt, and 22.0 ppt, respectively, in the global background atmosphere [ Carpenter et al , ]. In addition to these abundant HCFCs, there are a number of minor HCFCs, such as HCFC‐133a (C 2 H 2 ClF 3 ) [ Laube et al , ] and HCFC‐225ca (C 3 HCl 2 F 5 ) [ Kloss et al , ], which were observed recently in the current atmosphere or in archived air samples. Despite the Montreal Protocol regulations for developed countries, most of these HCFCs are still increasing in the troposphere, due to the allowed, growing use in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…It is apparent that both the aircraft and the balloon data follow the ground-based trends quite well for all six gases. Slightly enhanced mixing ratios can often be observed in the vicinity of the tropopause, mostly due to recent influences from regional emissions (Kloss et al, 2014, Leedham Elvidge et al, 2015, Oram et al, 2017. This is especially pronounced in the research aircraft data from 2017, which belong to a campaign (Höpfner et al, 2019) exploring the atmospheric composition above the polluted Asian Monsoon region (Randel et al, 2010, Vogel et al, 2019.…”
Section: Observational Data Overview and Comparisonsmentioning
confidence: 99%